Burden of chronic spontaneous urticaria in Italy through healthcare resource utilization and direct costs: a retrospective analysis of real-world using administrative healthcare data - Giulia Ronconi; Letizia Dondi; Silvia Calabria; Leonardo Dondi; Irene Dell’Anno; Lucia Casoli; Diletta Valsecchi; Ornella Bonavita; Eustachio Nettis; Nello Martini; Carlo Piccinni (BMC Health Services Research)
Abstract Background Chronic spontaneous urticaria (CSU) is a disorder of skin and mucosal tissues lasting at least 6 weeks. Treatments are primarily addressed to reduce symptoms; therefore, patients still experience poor living conditions and high unmet needs. This retrospective observational study was aimed to describe patients newly diagnosed with CSU, their healthcare resource utilization and related economic burden through Italian administrative healthcare data. Methods From a large Italian administrative healthcare database (˜5.5 million inhabitants/year), in- and outpatients newly diagnosed with CSU from January 1st, 2016, to December 31st, 2021 (index date) were identified through specific algorithms. Drug dispensations, overnight hospitalizations, emergency department (ED) accesses, local outpatient specialist care and direct costs charged to the Italian National Health Service (SSN) were described throughout the first follow-up year. Also, CSU exacerbations were assessed throughout the available follow-up/patient (variable based on the accrual year and up to December 31st 2022). Results Patients newly diagnosed with CSU in Italy were 1,707. The median (IQR) age was 36 (18;55) years with twice as many females as males. Cardiometabolic diseases were the most common comorbidities. Throughout the first follow-up year: 72.9% patients were treated with second-generation H1-antihistamines (mainly cetirizine), 19.5% with omalizumab; concomitantly, 55.5% received oral corticosteroids (OCS), and 25.0% non-steroidal antiinflammatory drugs. At least one CSU exacerbation occurred in 81.2% patients; of them, only one third were treated with omalizumab on average 10.9 months following exacerbation. New users of omalizumab during the available follow-ups were 30.6% patients. On average, 1.6 overnight hospitalizations occurred to 16.8% of patients mainly because of urticaria and angioedema. At least one local outpatient specialist service was performed to 78.6% patients; 63.3% were examined by a specialist, on average 3 times during the first year. The mean per patient annual total expenditure was €1901, of which 45.4% was due to pharmaceuticals. Conclusions During the first year following the new CSU diagnosis, a lower than recommended antihistamines dispensation while an elevated use of OCS and a low and delayed omalizumab initiation after CSU exacerbation were observed, suggesting the urgent need to optimize treatment management to limit the burden on patients and healthcare systems.